Environmental sustainability with the role of green innovation and economic growth in India with bootstrap ARDL approach - Pachiyappan, Duraisamy; Alam, Md Shabbir; Khan, Uzma; Khan, Aarif Mohammed; Mohammed, Shariq; Alagirisamy, Kuppusamy; Manigandan, Palanisamy (Frontiers in Environmental Science, 2022)
There is no evidence of cointegration between green innovation, economic growth, drama and film, and carbon emissions in nations. This paper applies a novel Bootstrap Autoregressive Distributed Lag (BARDL) approach to investigate the relationship between green innovation, economic growth (GDP), drama and film industry, and India's environmental Sustainability from 2000 to 2018 period. The data has been checked for its stationarity by applying the Zivot and Andrews (ZA) unit root test. The cointegration test results suggest a long-run equilibrium relationship between the variables. The empirical finding of long-run estimates reveals that 1% augments in green innovation, economic growth, and drama and film industry increase carbon emissions by -0.075, 0.503%, and 0.113%, respectively. Furthermore, our results indicate that economic growth, drama, and the film industry have statistically significant positive effects on CO2 emissions, and green innovation have statistically significant adverse effects on CO2 emissions. Green innovation leads to lower environmental damage by reducing carbon emissions. Based on the finding of this study, policy implications are suggested for India.